The Causes of Chest Pain in Children and the Criteria for Targeted Myocardial Enzyme Testing in Identifying the Causes of Chest Pain in Children - Chen, Li; Duan, Hongzhou; Li, Xiaoyan; Yang, Zuozhen; Jiao, Meng; Sun, Kangtai; Jin, Mei (Frontiers in Cardiovascular Medicine, 2021)
Aims Chest pain is a common complaint at pediatric cardiology clinics and often leads to an extensive cardiac evaluation. In this study, we analyzed the causes of chest pain in Chinese children and developed diagnostic procedures and criteria for targeted myocardial enzyme testing. Methods and Results We retrospectively analyzed the clinical data of patients aged below 18 years visiting our hospital for chest pain between 2005 and 2019. Based on auxiliary exams and clinical diagnosis, we developed diagnostic procedures and criteria for targeted myocardial enzyme testing in children with chest pain. A total of 7251 children were included in this study. The chest pain was of cardiac origin in 581 patients (8.0%). The incidence of noncardiac chest pain was significantly higher in the preschool group and the school-age group than in the adolescent group (93.5% vs 93.8% vs 90.3%, P < 0.05). Among children with cardiac chest pain, the most common concomitant symptom was chest tightness (67.0%). Myocardial enzyme testing was performed in 5408 patients and was abnormal in 453 patients. We developed a diagnostic procedure and criteria for targeted myocardial enzyme testing using pertinent history, physical examination, and ECG findings or UCG finding. Applying the diagnostic procedure and criteria could lead to the reduction in myocardial enzyme testing while still capturing all cardiac diagnoses. Conclusion In children, chest pain is mostly benign and rarely cardiac. During diagnosis, targeted myocardial enzyme testing based on medical history and physical examination can effectively reduce resource use.